Yo-Yo Intermittent Endurance Test-Level 1 to monitor changes in aerobic fitness in pre-pubertal boys. Issue 2 (17th February 2016) - Fernandes, Luís; Krustrup, Peter; Silva, Gustavo; Rebelo, Antonio; Oliveira, José; Brito, João
Abstract: The present study aimed to examine the performance and heart rate responses during the Yo-Yo Intermittent Endurance Test-Level 1 (Yo-Yo IE1) in children under the age of 10. One hundred and seven male children (7–9 years) performed the Yo-Yo IE1 at the beginning (M1 ), middle (M2 ) and end (M3 ) of the school year. Data from individual heart rate curves of the Yo-Yo IE1 were analysed in order to detect the inflection point between an initial phase of fast rise in heart rate values and a second phase in which the rise of the heart rate values is much smaller. The distance covered in the Yo-Yo IE1 improved from M1 to M3 (884 ± 496 vs. 1032 ± 596 m; p < 0.05; d = 0.27), with intermediate values for M2 (962 ± 528 m). Peak heart rate (HRpeak ) decreased from M1 to M2 and M3 (204 ± 9, 202 ± 9 and 200 ± 9 bpm, respectively; p < 0.05; d = 0.25–0.42). The 7th shuttle of the test (280 m), corresponding to 2.5 min, was identified as the inflection point between the two phases. Also, absolute heart rate at the 7th shuttle decreased progressively throughout the year (185 ± 9, 183 ± 10, and 179 ± 10 bpm; p < 0.05; d = 0.31–0.61). The present study provides evidence of the usefulness of a maximal as well as a submaximal version of Yo-Yo IE1 as a tool to monitor changes in aerobic fitness in pre-pubertal children.